Enhancing Clinical Diagnosis for Patients With Persistent Pulmonary Abnormalities After COVID-19 Infection: The Potential Benefit of 68Ga-FAPI PET/CT. (15th December 2022) - Sviridenko, Anna; Boehm, Anna; di Santo, Gianpaolo; Uprimny, Christian; Nilica, Bernhard; Fritz, Josef; Giesel, Frederik L.; Haberkorn, Uwe; Sahanic, Sabina; Decristoforo, Clemens; Tancevski, Ivan; Widmann, Gerlig; et al.
Abstract: Coronavirus disease 2019 (COVID-19)–related pneumonia challenges clinical practice. We explore the potential diagnostic benefit of PET/CT to establish the underlying inflammatory or fibrotic repair processes in prolonged structural lung abnormalities in COVID-19 patients. Patients and Methods: Six post COVID-19 patients suspected for pulmonary fibrosis were scheduled for dual-tracer PET/CT with 18 F-FDG and 68 Ga–fibroblast activation protein inhibitor (FAPI)–46. The uptake of 68 Ga-FAPI-46 in the involved lung was compared with a control group of 9 non–COVID-19 patients. Clinical data and PET/CT imaging were collected and analyzed. Results: PET/CT revealed in all 6 pulmonary impaired patients the reduced glucose avidity on 18 F-FDG and clear positivity on 68 Ga-FAPI-46 PET/CT in comparison to the control group. Conclusions: Enhancing fibrotic repair mechanisms, 68 Ga-FAPI PET/CT may improve noninvasive clinical diagnostic performance in patients with long-term CT abnormalities after severe COVID-19. Although this study shows promising results, additional studies in larger populations are required to establish a general diagnostic guideline.